Prevalence of asthma symptoms in Latin America: the International Study of Asthma and Allergies in Childhood (ISAAC). - Mallol, J (2000)
The prevalence of respiratory symptoms indicative of asthma in children from Latin America has been largely ignored. As part of the International Study of Asthma and Allergies in Childhood (ISAAC), 17 centers in 9 different Latin American countries participated in the study, and data from 52,549 written questionnaires (WQ) in children aged 13-14 years and from 36,264 WQ in 6-7 year olds are described here. In children aged 13-14 years, the prevalence of asthma ever ranged from 5.5-28%, and the prevalence of wheezing in the last 12 months from 6.6-27%. In children aged 6-7 years, the prevalence of asthma ever ranged from 4.1-26.9%, and the prevalence of wheezing in the last 12 months ranged from 8.6-32.1%. The lower prevalence in centers with higher levels of atmospheric pollution suggests that chronic inhalation of polluted air in children does not contribute to asthma. Furthermore, the high figures for asthma in a region with a high level of gastrointestinal parasite infestation, and a high burden of acute respiratory infections occurring early in life, suggest that these factors, considered as protective in other regions, do not have the same effect in this region. The present study indicates that the prevalence of asthma and related symptoms in Latin America is as high and variable as described in industrialized or developed regions of the world.